PENGARUH DANA ALOKASI UMUM (DAU), DANA ALOKASI KHUSUS (DAK), PENDAPATAN ASLI DAERAH (PAD), DANA BAGI HASIL (DBH), BANTUAN KEUANGAN PROVINSI (BKP) TERHADAP IPM DENGAN BELANJA PELAYANAN DASAR (BPD) SEBAGAI MODERATING VARIABEL - Atanasius Widarwanto; Erliana Erliana; Idhar Yahya (Jurnal Telaah dan Riset Akuntansi, 2014)
ABSTACT The objective of the study was to analyze the influence of DAU, DAK, PAD, DBH, and BKP on IPM partially and simultaneously. Besides that, the research analyzed the influence of DAU, DAK, PAD, DBH, and BKP on IPM with BPD as moderating variable. The data were analyzed quantitatively by using generalized linear regression analysis, pooled data panel fixed effect method, and classic assumption test before the best research model was obtained. Independent variables were DAU, DAK, PAD, DBH, and BKP, while BPD was moderating variable and IPM was dependent variable. The samples consisted of 30 District/Town Administrations in the period of 2009-2012. The result of the research showed that, simultaneously, the variables of DAU, DAK, PAD, DBH, and BKP influenced IPM; partially, DAK and BKP did not have any influence on IPM. This was in line with the result of the research conducted by Setyowati and Suparwati (2012) which pointed out that DAU, DAK, and PAD had positive influence on IPM through PABM (Allocation of Capital Expenditures). It was also concluded that BPD played its role as moderating variable in strengthening and weakening the correlation of DAU, DAK, PAD, DBH, and BKP with IPM. Keywords: DAU (Block Grant), DAK (Special Grant), PAD (Regional Generated Revenues), DBH (Profit Sharing Fund), BKP (Provincial Financing Aid), IPM (Human Development Index), BPD (Basic Service Expenditures).